1997
DOI: 10.1111/j.1365-2044.1997.254-az0387.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of position on autonomic nervous activity in late pregnancy

Abstract: SummaryWe investigated the effect of three different recumbent positions on autonomic nervous activity in late pregnancy. Thirty pregnant and 24 nonpregnant aged-matched women were studied, and measures of heart rate variability in both time and frequency domains were compared using supine, right and left lateral decubitus positions. In the nonpregnant women, the normalised highfrequency power was greatest in the right lateral decubitus position. In the pregnant women, the normalised high-frequency power was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 10 publications
0
31
0
1
Order By: Relevance
“…In the last few decades, several studies have suggested that pregnant women should be sited in the lateral position during the whole fetal MRI examination to avoid the development of VCCS, particularly to avoid severe forms of VCCS that can lead to cardiovascular decompensation [8,13,15,17]. These recommendations are based on studies dealing with the topic of VCCS in pregnant women using different invasive and noninvasive methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few decades, several studies have suggested that pregnant women should be sited in the lateral position during the whole fetal MRI examination to avoid the development of VCCS, particularly to avoid severe forms of VCCS that can lead to cardiovascular decompensation [8,13,15,17]. These recommendations are based on studies dealing with the topic of VCCS in pregnant women using different invasive and noninvasive methods.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms predominantly occur in the supine position [7]. With regard to the prevention of VCCS, it is recommended that supine positioning of pregnant women during any kind of lengthy diagnostic or therapeutic intervention should be avoided [6,8,15]. This recommendation applies particularly to the evolving technique of fetal magnetic resonance imaging (MRI), where examination times of up to 45 min are often necessary to obtain a complete and diagnostic set of images of the third-trimester fetus [18].…”
Section: Introductionmentioning
confidence: 96%
“…The HRV analysis was performed in the same way as in our previous study [9,10]. In brief, the mean, standard deviation (SD) and coefficient of variation of 512 RR intervals were calculated using standard formulae.…”
Section: Methodsmentioning
confidence: 99%
“…Lateral tilt was suggested as a means of relieving compression of the inferior vena cava and improving cardiac output [7]. By using HRV analysis, the supine position was found to have the least cardiac vagal activity and the greatest sympathetic activity in three recumbent positions [9]. To evaluate further the effect of aortocaval compression on autonomic nervous activity, we compared the autonomic nervous activity in the supine and upright positions in nonpregnant women with those in women in late pregnancy.…”
mentioning
confidence: 99%
“…Ventilation may also produce some discomfort to the mother due to elevation of the diaphragm and other known ventilatory changes, such as the increase of CO 2 and hypoxia sensitivity, of respiratory drive, and of respiratory impedance [4,5]. Finally, supine position may exert inappropriate stimulatory effects on the autonomic nervous system, due to the aorto-caval compression [6][7][8]. Therefore, in theory, the reduction of fetal weight by a microgravity environment may relieve some of the above-mentioned discomforts of pregnancy.…”
Section: Introductionmentioning
confidence: 97%